Die Zukunft der Vergangenheit in der Gegenwart: Archive als Leuchtfeuer im Informationszeitalter (2019)
The volume contains 18 contributions to an international conference of archivists and historians dealing with the current situation of archives and archival science generally and specifically with the impact of digitization on archival core tasks and on the societal roles of archives.